Biocorrosion at Embalse Nuclear Power Plant. Analysis of the Effect of a Biocide Product. (2015) - Giacobone, Ana F. Forte; Pizarro, Ramon A.; Rodríguez, Sebastian A.; Belloni, Mauro; Croatto, Federico J.; Ferrari, Franco; Herrera, Cecilia; Mendizábal, Maria I.; Montes, Juan; Aliciardi, Matias Rodríguez; Saucedo, Ramona; Ovando, Luis E.; et al.
Abstract: Biocorrosion refers to the influence of microorganisms adhered to surfaces, in the corrosion process of metals. At Embalse Nuclear Power Plant (ENPP), this phenomenon has been detected in several water cooling systems. In order to mitigate this process, it was proposed to modify the current chlorination water treatment by adding a commercial bromide-based biocide. This study evaluated in situ the effect of the addition of the biocide on biofilm formation and also on the corrosion rate of carbon steel components. The results of the corrosion rate measurements, as well as the evaluation of the kinetics of biofilm growth, showed no significant difference between the former and the modified water treatments. It was concluded that, under the current conditions of operation, the addition of a bromide-based biocide (BBB) does not improve the effectiveness against biofouling and biocorrosion of the water treatment.